2022
DOI: 10.20961/soja.v2i2.58950
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Enhanced Recovery After Caesarean Section (ERACS) in Elective Procedure : A Case Report

Abstract: <p><strong>Background</strong>: Enhanced Recovery After Cesarean Section (ERACS) protocol includes every component of the pre-operative, intra-operative and post-operative pathway. In the pre-operative phase, the protocol applied to this patient included the shortest possible fasting interval, oral intake of liquid carbohydrate and patient counselling. For intra-operative pathway, the components applied are prevention of hypotension, maintenance of normothermia, optimal uterotonic administrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
(4 reference statements)
0
2
0
Order By: Relevance
“…Almost all of the studies mentioned the high patient satisfaction by using ERACS. In detail, it reports the decreasing level of pain (Mauliza et al, 2022;Millizia et al, 2023;Rahayu et al, 2023;Ruspita et al, 2023), accelerating early mobilization (Adha & Anita, 2023;Mauliza et al, 2022;Millizia et al, 2023), reducing infection and complications (Raharja & Aini, 2023;Ruspita et al, 2023;Sardimon et al, 2022;Uhud et al, 2023), and reducing postoperative length of stay (LoS) (Raharja & Aini, 2023;Sardimon et al, 2022). However, some studies also revealed the weakness and side effects of ERACS including ineffective for accelerating colostrum exertion (Rahayu et al, 2023) and less than half of respondents felt nausea, vomiting, and chills (Mauliza et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Almost all of the studies mentioned the high patient satisfaction by using ERACS. In detail, it reports the decreasing level of pain (Mauliza et al, 2022;Millizia et al, 2023;Rahayu et al, 2023;Ruspita et al, 2023), accelerating early mobilization (Adha & Anita, 2023;Mauliza et al, 2022;Millizia et al, 2023), reducing infection and complications (Raharja & Aini, 2023;Ruspita et al, 2023;Sardimon et al, 2022;Uhud et al, 2023), and reducing postoperative length of stay (LoS) (Raharja & Aini, 2023;Sardimon et al, 2022). However, some studies also revealed the weakness and side effects of ERACS including ineffective for accelerating colostrum exertion (Rahayu et al, 2023) and less than half of respondents felt nausea, vomiting, and chills (Mauliza et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…The guidelines for postoperative care in cesarean delivery have created a pathway for postoperative care, emphasizing the importance of a comprehensive approach to recovery (Macones et al, 2019). Furthermore, the implementation of ERACS in elective procedures has been reported, highlighting the incorporation of the protocol into clinical practice in Indonesia (Sardimon et al, 2022). The guidelines and case report provide valuable insights into the implementation and impact of ERACS in the Indonesian healthcare setting.…”
Section: Resultsmentioning
confidence: 99%